Biometria de frutos e sementes, superação de dormência e germinação de Senegalia tenuifolia (L.) Britton & Rose - Araújo, Alcimone Maria Silva (Universidade Federal Rural do Semi-Árido, 2014)
The Senegalia tenuifolia species is part of the native vegetation of the northeastern semiarid, belonging to the family of Fabaceae (Mimosoideae) is commonly known as cat's claw, saw throat or Calumbi. The objective of this research was to characterize the seed and germination potential of the species. For the characterization of seed, held biometrics using a random sample of 100 and 10 0 seeds and fruits were evaluated: weight, l ength, width and thickness of fruits and seeds , and the number of seeds pro fruit. Monitoring the imbibition curve with the ends removed and intact seeds were performed in the opposite region to the embryonic axis. Witness, lopping , scarification with sandpaper, soaking fo r 12, 24 and 48 hours hot water: The assessment of seed germination, twelve pre-germination treatments to evaluate seed dormancy and germination rate with the following treatments were evaluated 80°C for 3, 6 and 12 minutes and sulfuric acid for 3, 6 and 12 minutes. The seeds were germinated on paper germitest under BOD chamber. The germination was also assessed to test the effect of substrate temperature on germination resulting from the combination of the substrates on paper, on sand and vermiculite paper roll and under three temperatures: 25°C, 30 °C and 35°C in a factorial 4x3. In biometrics, a descriptive analysis of the data was performed by frequency, maximum and minimum, standard deviation and range. The design for the pre -germination treatments and germination test was used completely randomized design with four replications of 25 seeds each. Data were submitted to analysis of variance and the treatment means were compared by Tukey test at 5% probability. The biometric analyzes showed low variation for both fruits and seeds to. The curve of water uptake by seeds presented triphasic model with stage III occurring in the 21st minute soaking. For pre-germinative seed treatments Calumbi the cutting in the opposite embryonic axis sandpaper and sulfuric acid for 3 minutes, with values of 97, 91 and 88%, respectively region. To calculate the index of germination speed that got the best result was sulfuric acid for 6 minutes with a value of 17.7. A temperature of 25 to 30ºC, regardless of the substrate used, was the most suitable for germination in seeds of Senegalia tenuifolia
Biometrics of fruits and seeds, overcoming dormancy and germination Senegalia tenuifolia (L.) Britton & Rose
Keywords: Soaking; Semiarido; Substrate; Temperature; Embebição; Semiárido; Substrato; Temperatura; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL